Label-Free Imaging of Basement Membranes Differentiates Normal, Precancerous, and Cancerous Colonic Tissues by Second-Harmonic Generation Microscopy - Zhuo, Shuangmu; Yan, Jun; Chen, Gang; Shi, Hong; Zhu, Xiaoqin; Lu, Jianping; Chen, Jianxin; Xie, Shusen (PLOS ONE, 2012)
Since changes in the basement membranes are the critical indicators for differentiating normal, precancerous, and cancerous colonic tissues, direct visualization of these warning signs is essential for the early diagnosis and treatment of colonic cancer. Here, we present that second harmonic generation (SHG) microscopy can probe the changes of basement membranes in different colonic cancer stages. Our results also show the capability of using the quantitative analyses of images for quantifying these changes in different cancer stages. These results suggest that SHG microscopy has the potential in label-freely imaging the changes of basement membranes for effectively distinguishing between normal, precancerous, and cancerous colonic tissues. To our knowledge, this is the first demonstration of the dynamics of basement membrane changes in different colonic cancer stages using entirely intrinsic source of contrast.